Legal boundaries of digital identity creation - Ewa Michalkiewicz-Kadziela; Ewa Milczarek (Internet Policy Review, 2021)
The internet has created possibilities to define human identity in a digital world. This entails the need to consider the impact of this new environment of identity's operation and the effects of possible differences. The authors analyse digital identity in terms of its relation with human identity derived from Article 8 of the Convention for the Protection of Human Rights and Fundamental Freedoms. The paper's research goal is to specify the relation between digital identity and real identity, aiming in essence to provide an answer to the following research question: does the internet as the new sphere of identity's operation have such an effect that it created a need to specify a legal framework and methods of protection unique to digital identity? This study aims to specify legal tools for creating digital identity and the legal boundaries of the possible creation.
Keywords: 300; Identity; Human rights; Digital identity; EU law; Avatars